Tranexemic acid induced bilateral acute renal cortical necrosis: An autopsy case report - Londhe, Mangesh Machindra; Gadgil, Nitin M; Padmanabhan, Anitha; Naik, Leena Pravin (Annals of Pathology and Laboratory Medicine, 2019)
Acute renal cortical necrosis (RCN) most commonly occurs from obstetric complications. However other rare cause includes medications like antifibrinolytics like tranexamic acid, which is used for acute bleeding. We report a case of 17 years female, operated for left cheek arteriovenous malformation and managed post-operatively by intravenous fluids, diuretics, antibiotics and antifibrinolytics (tranexemic acid). Postoperatively she started complaining of severe abdominal pain, breathlessness, weakness and loss of orientation with increasing levels of serum creatinine and blood urea nitrogen (BUN). Patient succumbed to death on day 6 post operative and complete autopsy was performed. All organs were unremarkable except bilateral lungs showed pulmonary edema and bilateral kidneys showed features of diffuse pattern of cortical necrosis both on gross and histopathological examination. As patient had no obstetric or other related history the cause of RCN was attributed to tranexemic acid. Thus patients on antifibrinolytics must be screened for RCN to avoid its fatal complication.